2014
DOI: 10.1007/s12013-014-9830-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Novel Photosensitizer DTPP with 650 nm Laser Results in Efficient Apoptosis and Cytoskeleton Collapse in Breast Cancer MCF-7 Cells

Abstract: Luminal A type breast cancer was suitable for Photodynamic therapy (PDT) as its strong adhesion ability, low malignancy and easily being exposed to laser. To examine the novel photosensitizer agent 5-5-(4-N, N-diacetoxylphenyl-10, 15, 20-tetraphenylporphyrin)(DTPP) mediate PDT in breast cancer cell, Luminal A type breast cancer MCF-7 cells were used in this study, various concentrations of DTPP (0, 2, 4, 6, 8, 10, 12, 15, 20, 25, 30 μg/mL) and different time intervals (0, 0.5, 1, 2, 4, 6, 8 min) of laser expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Actin has been identified as the main cytoskeleton component affected by PDT either at the early or at the late stages of photodamage. [3][4][5][6][7][8][9]22,23,27,28 However, the changes induced in the structure of actin filaments seem to depend on the initial morphology of the cell. The 5-aminolevulinic acid (ALA)-PDT has been proven to increase the number of stress fibres on human adenocarcinoma WiDr cells, which grow in dense colonies, whereas it caused loss of fibrillar actin structures in growth cones of D54Mg cells, which grow separately.…”
Section: Microfilamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin has been identified as the main cytoskeleton component affected by PDT either at the early or at the late stages of photodamage. [3][4][5][6][7][8][9]22,23,27,28 However, the changes induced in the structure of actin filaments seem to depend on the initial morphology of the cell. The 5-aminolevulinic acid (ALA)-PDT has been proven to increase the number of stress fibres on human adenocarcinoma WiDr cells, which grow in dense colonies, whereas it caused loss of fibrillar actin structures in growth cones of D54Mg cells, which grow separately.…”
Section: Microfilamentsmentioning
confidence: 99%
“…In vitro, a decreased invasive and migratory phenotype of PDT-treated cells has been reported for a wide range of photosensitisers. 16,23,27,101,[104][105][106][107][108] On the other hand, the migration of mesenchymal stem cells towards glioblastoma cells was enhanced after ALA-PDT treatment. 109 HPD-PDT decreased adhesiveness of cancer cells to endothelial cells in vitro, has been found to correlate with a decreased metastatic potential of HPD-PDT treated cells injected into rats.…”
Section: Metastasismentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a technique currently used to treat malignant tumors , and microbial parasites . It is based on three key components: a photosensitizer, a light source, and tissue oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Their data have shown that DTPP arrested CC at S phase, leading to cytoskeleton collapse. Moreover, they investigated DTPP on MCF-7 cells and concluded that DTPP arrests growth and microtubule alteration of MCF-7 cells at 4 μg/ml concentration ( 129 , 130 ). Moreover, tetra-(4-carboxyphenoxy) phthalocyanine zinc (TαPcZn), a novel hydrophilic/lipophilic PS designed and synthesized by Xia et al.…”
Section: Cca Following Pdtmentioning
confidence: 99%